Optimal Portfolio Formation Analysis vs. Single Index Model: 2018–2019 Before Crisis and 2020–21 During Crisis - Uska Wyanov; Imo Gandakusuma (Jurnal Manajemen Bisnis, 2023)
This paper focuses on a portfolio comparison analysis between 30 leading board stocks and 30 development board stocks selected from the Indonesia Stock Exchange (IDX). The analysis used in this study is the single index model. The periods used in this study are 2018-2019 (before the crisis) and 2020-2021 (during the crisis). The research results concluded that the Development Board stock group generated a higher portfolio return compared to the Main Board stock group, both in the 2018-2019 period (before the crisis) and in the 2020-2021 period (during the crisis). However, even though it produces a higher portfolio return, the Development Board stock group also has a higher level of portfolio risk compared to the Main Board stock group.